Agama dan Perspektif Dale Cannon Mengenai Agama - Sandro Apriedo; Listia Septiana; Juan Andika Manuputty; Sarmauli Sarmauli (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
Every existing religion has procedures, systems, practices, rituals and rules that must be followed by its adherents. This article describes the opinions of experts regarding religion and Dale Cannon's ideas about the six main ways of being religious as written in his book Six Ways of Being Religious. These six ways can be found in almost every existing religion, the six ways are as follows: The Way of Scared Rite, The Way of Right Action, The Way of Devotion , The Way of Shamanic Meditation, The Way of Mystical Quest, The Way of Reasoned Inquiry.